Self-Interest, prosociality, and the moral cognition of markets: A comparative analysis of the Theory of Moral Sentiments and the Wealth of Nations - Acerbi, Alberto; Sacco, Pier Luigi (Rationality and society, 2023)
In this paper, we perform a text analysis of Adam Smith’s two books, the Theory of Moral Sentiments and the Wealth of Nations, to better characterize their highly disputed differences in terms of moral cognition. In particular, given that Smith’s ideas are still very cited and influential in the current scholarly debate on moral cognition, we are interested in understanding whether a text analysis would unveil a semantic structure that is in line with a dual process theory interpretation or, alternatively, with a neuro-emergent cognition one. We find that, despite that the intellectual koine in which Smith’s thought was originally embedded would be more in line with a dual process theory approach, the analysis reveals a better consonance with the neuro-emergent cognition approach. This opens new and interesting perspectives in future research on the moral cognition of market interactions in a Smithian tradition of thought.